Overview of the Incidence of Post Operative Nausea and Vomiting in Spinal Anesthesia for Sectio Caesarea Patients in the Recovery Room of Fatimah Cilacap Islamic Hospital - Nurdiamsyah, Pratomo; Susanto, Amin; Burhan, Asmat; Suandika, Made; Wijayanti, Indri (Java Nursing Journal, 2024)
Background: Post operative nausea vomiting (PONV) is nausea and vomiting that occurs after surgery and before the patient returns from the hospital. PONV must be taken seriously because it can have an impact on the length of the patient's recovery period, hamper activities, and increase the cost of care that must be incurred. PONV or nausea and vomiting. Aim: what is the description of the incidence of PONV in spinal anesthesia in SC patients in the recovery room (RR) RSI Fatimah Cilacap. Method: Quantitative descriptive with a cross section approach, the sample used total sampling of 31 respondents instruments using the Simplified Postoperative Nausea and Vomiting Impact Scale for Audit and Post-Discharge. Findings: PONV sufferers were 19 respondents (59.4%), based on age 26-34 years as many as 16 respondents (51.6%), at BMI the incidence of PONV was obese as many as 11 respondents (35.5%), in the length of surgery the most PONV was found in women as many as 4 respondents (11.4%), in the length of surgery the incidence of PONV was found to be mostly 1-2 hours as many as 10 respondents (32.3%), and in the previous PONV history the incidence of PONV was found to have all experienced PONV before as many as 13 respondents (16.1%). Conclusion: the frequency distribution of PONV incidence on respondents who are female, obese IMT operation duration and PONV history with spinal anesthesia technique in cesarean section surgery.